Body mass index and B‐lines on lung ultrasonography in chronic and acute heart failure - Philip Brainin; Brian Claggett; Eldrin F. Lewis; Kristin H. Dwyer; Allison A. Merz; Montane B. Silverman; Varsha Swamy; Tor Biering‐Sørensen; Jose Rivero; Susan Cheng; John J.V. McMurray; Scott D. Solomon; et al. (ESC Heart Failure)
Abstract Aims Increased body mass index (BMI) is common in heart failure (HF) patients and is associated with lower levels of N‐terminal pro‐brain natriuretic peptide (NT‐proBNP). We evaluated the influence of BMI on lung ultrasonography (LUS) findings indicative of pulmonary congestion (i.e. B‐lines) in patients with chronic and acute HF (AHF). Methods and results We analysed ambulatory chronic HF (n = 118) and hospitalized AHF (n = 177) patients (mean age 70 years, 64% men, mean BMI 29 kg/m2, mean ejection fraction 42%) undergoing echocardiography and LUS in eight chest zones. B‐lines and chest wall thickness (skin to pleura) on ultrasound were quantified offline and blinded to clinical findings. NT‐proBNP was available in AHF patients (n = 167). In chronic HF, B‐line number decreased by 18% per 5 unit increase in BMI [95% confidence interval (CI) −35% to +5%, P = 0.11]. In AHF, the number of B‐lines decreased by 12% per 5 unit increase in BMI (95% CI −19% to −5%, P = 0.001), whereas NT‐proBNP concentration decreased by 28% per 5 unit increase in BMI (95% CI −40% to −16%, P < 0.001). For AHF, B‐line number declined to a lesser degree than NT‐proBNP concentration with increasing BMI (P = 0.020), and >6 B‐lines were observed in half of AHF patients with severe obesity. There was an inverse relationship between B‐line number and chest wall thickness, and this association varied by chest region. Conclusions Despite an inverse relationship between B‐lines and BMI, B‐lines declined to a lesser degree than NT‐proBNP with increasing BMI. These data suggest that LUS may be useful in patients with HF despite obesity.